2013
DOI: 10.1002/er.3052
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of P-doped and V-doped Fe2O3for renewable energy conversion

Abstract: SUMMARYThe effect of P and V contents on the microstructure and thermoelectric properties of Fe 2-x M x O 3 (M: P and V; 0 ≤ x ≤ 0.01) is studied. Higher P and V contents result in increases of both the grain size and density, thus increasing the electrical conductivity. The absolute values of the Seebeck coefficients of the Fe 2-x P x O 3 and Fe 2-x V x O 3 increase with increasing P and V contents up to x = 0.0075 and 0.005, respectively, and then decrease with further increase of its concentration. The addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Foreign ion doping is a widely used method for metal oxides to improve the intrinsic electrical conductivity . Recently, Lu et al .…”
Section: Intrinsic Modifications Of Iron Oxides/hydroxidesmentioning
confidence: 99%
“…Foreign ion doping is a widely used method for metal oxides to improve the intrinsic electrical conductivity . Recently, Lu et al .…”
Section: Intrinsic Modifications Of Iron Oxides/hydroxidesmentioning
confidence: 99%
“…In this part of the study, the effect of changing the compression ratio (8,10,12) will be shown, which is the most common for SI engines. As the compression ratio increases, the temperature of the combustion gases increases, due to the increase of the pressure of the combustion gases.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers [6][7][8][9][10][11] in literature studied the usage of the TEG on the AWHRAs versus many factors to get better performance. The most used locations according to literature are the radiator and the exhaust pipe.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the value of PF is frequently used in the development of thermoelectric materials. 29,41,42) Figure 9(a) shows the relationships between R and S in this study. Increasing the oxidation temperature produced increases not only in S but also in R. Therefore, a good correlation between R and S can be seen in Fig.…”
Section: Estimation Of Maximum Powermentioning
confidence: 89%